Combination of Superficial Keratectomy, Ethylenediaminetetraacetic (EDTA), and Amniotic Membrane Transplantation as A Treatment of Band keratopathy: A Case Report: Poster Presentation - Case Report - Resident - Ilmah; Patriotika Muslima; Elfa Ali Idrus; Arief Akhdestira Mustaram; Angga Fajriansyah (Majalah Oftalmologi Indonesia, 2023)
Introduction : Band keratopathy is a degeneration of the cornea characterized by the presence of opacity, which isa deposit of calcium hydroxyapatite. These calcium deposits can be removed in several ways, including using ethylenediaminetetraacetic (EDTA), superficial keratectomy, or phototherapy keratectomy. Case Illustration : A 29-year-old male patient came with complaints of blurry vision in the right eye since 2-3 years ago, accompanied by the middle part of both eyes looking white, especially the right eye, since 17 years ago. The examination revealed a band keratopathy in the nasal to temporal region with neovascularization in the right eye, and keratopathy bands in the nasal and temporal parts, as wellas a cloudy lens in the right eye (Figure 1). Patients received treatment that included a combination of superficial keratectomy, administration of EDTA, and amniotic membrane transplantation (Figure 2). After the procedure, the clarity of the cornea improves (Figure 3). The patient was scheduled to undergo cataract surgery on his right eye. Discussion : Band keratopathy is a degenerative condition of the cornea characterized by grayish-white hazy deposits in the superficial layers of the cornea, primarily affecting Bowman's layer. In the treatment of individuals with symptomatic band keratopathy, chelation with EDTA, superficial keratectomy, laser keratectomy for phototherapy, or combining current procedures are the most often utilized therapeutic approaches. Conclusion : The combination of surgical management in cases of band keratopathy is expected to remove deposits on the cornea, improve the ocular surface, and reduce recurrences.